Comparative study of Fish Amino acid (FAA) & Soybean amino acid as foliar application on Spinach (Spinacia oleracea) L. - Kulbhushan W. Pawar, (The Bioscan, 2025)
An experiment was conducted to determine the effects of fish amino acid (FAA) and soybean amino acid application on the growth and development of spinach (Spinacia oleracea L.) during various sampling times. An experimental design was employed, wherein spinach plants were subjected to foliar applications of FAA and soybean amino acid (SAA). Control groups without amino acid treatments were also maintained for comparative analysis. The treatments were applied at specific growth stages, and their impacts on plant height, leaf area, chlorophyll content, biomass, and yield were assessed. Results indicated that both FAA and SAA significantly improved the growth parameters of spinach compared to the control groups. However, FAA demonstrated a slightly superior effect on overall plant vigor, leaf chlorophyll content, and yield in both crops. The enhanced performance of FAA could be attributed to its diverse amino acid profile and the presence of additional bioactive compounds inherent to fish-derived products. The spinach plants were treated with varying concentrations of FAA and soybean amino acid, specifically 1.0% and 2.0%. Amino acids are derived from both plant-based and animal-based ingredients. The composition of fish with molasses and soybean with molasses in a 1:1 ratio undergoes fermentation. The fermentation process breaks down proteins into amino acids. Both mixtures were allowed to ferment for 30 days. Acetic acid bacteria were absent in both samples, while levels of lactic acid bacteria and yeast fluctuated. These findings were corroborated by visual analysis. Parameters such as root length, shoot length, and plant biomass were analyzed from the first week to the fourth week of planting. Results demonstrated that the application of FAA and soybean amino acid, along with different sampling times, significantly influenced shoot length, thereby promoting crop growth and enhancing spinach leaf development.